Problematika Orang Tua dalam Mendampingi Anak pada Pembelajaran Era pandemi Covid-19 - Ainun Mustarsyida; Erni Munastiwi (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to identify the problems of parents in assisting their children in learning during the COVID-19 pandemic. This study uses a qualitative method with a literature approach where in collecting information and data with documentation techniques and data on relevant matters from various sources in the library such as documents, books, magazines, news. The selection of news or articles can be classified based on discussion of COVID-19 and learning at home. This study was conducted to find various problems experienced by parents during the COVID-19 pandemic. The results of this study found the problems experienced by parents who were researchers divided into three groups, namely technology, mental, and role.